1989
DOI: 10.1200/jco.1989.7.9.1268
|View full text |Cite
|
Sign up to set email alerts
|

On the value of intensive remission-induction chemotherapy in elderly patients of 65+ years with acute myeloid leukemia: a randomized phase III study of the European Organization for Research and Treatment of Cancer Leukemia Group.

Abstract: We report the results of a prospective study in patients more than 65 years of age in whom two different therapeutic strategies were compared: immediate intensive-induction chemotherapy (arm A) versus "wait and see" and supportive care and mild cytoreductive chemotherapy only for relief of progressive acute myeloid leukemia (AML)-related symptoms (arm B). The major objective of the study was to compare survival outcome of both regimens. Thirty-one patients on arm A received one or two courses of daunorubicin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
202
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(215 citation statements)
references
References 15 publications
8
202
0
3
Order By: Relevance
“…Currently, there is no consensus on the optimal treatment for older patients with AML. Epidemiological and clinical studies have consistently demonstrated that AML patients up to 80 years old who are treated with intensive induction chemotherapy survive significantly longer than individuals receiving palliative care [39,40]. Despite this, many older individuals continue to be offered only low intensity or best supportive care due to concerns about treatment-related mortality and morbidity with intensive regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no consensus on the optimal treatment for older patients with AML. Epidemiological and clinical studies have consistently demonstrated that AML patients up to 80 years old who are treated with intensive induction chemotherapy survive significantly longer than individuals receiving palliative care [39,40]. Despite this, many older individuals continue to be offered only low intensity or best supportive care due to concerns about treatment-related mortality and morbidity with intensive regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Disease aggressiveness also impacts on therapy choice. When Lowenberg et al [39] randomized older AML patients to a "wait and see" approach instead of chemotherapy, they found that rapid disease progression leading to hyperleukocytosis and thrombocytopenia often necessitated initiation of cytoreductive therapy. Our study, as well as others, demonstrated that patients with high levels of surrogate markers reflective of increased cell turnover and tumor burden (specifically initial WBC, serum lactate dehydrogenase, and PB or BM blasts) preferentially receive IC as opposed to HMA or other lowintensity therapy [27,42].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of intensive compared with palliative therapy (with or without chemotherapy) are important to assess but difficult to address in clinical trials, and observation studies are unreliable because of large and uncontrolled patient selections. A small randomized study was published in 1989, in which 31 AML patients older than 65 years receiving combination chemotherapy had a median survival of 21 weeks compared with 11 weeks for 29 patients on a "wait-and-see" strategy, 27 and there was no difference in time spent in hospital. Another small study performed in the 1980s on 87 patients older than 65 years failed to show benefit from intensive therapy resulting from increased early death rates.…”
Section: Discussionmentioning
confidence: 99%
“…11 It also is not clear that induction therapy benefits older adults, with some prospective and retrospective analyses supporting the use of cytarabine-based ablative therapies, particularly in select subgroups of older adults, and others finding no clear benefit to dose intensification. [12][13][14][15] Further, potential improvements in outcome are often offset by treatment-related mortality associated with induction chemotherapy that may approach 25%, thus negating any survival benefit.…”
Section: Introductionmentioning
confidence: 99%